Integrating Ethnophysics and Mobile Technology: A Needs Analysis of Android-Based Learning Media Through North Maluku Traditional Dance - Irnin Agustina Dwi Astuti; Ria Asep Sumarni; Irawan Setiadi (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
Ternate has a variety of traditional dances passed down from generation to generation as a regional identity. One effort to preserve local culture is by integrating traditional dances into Physics learning through an ethnophysics approach. This study aims to identify the need for Android-based ethnophysics learning media to be used in Physics education. The needs analysis focused on students in one of the schools in Ternate, Indonesia. The data collection method used was quantitative, employing purposive sampling techniques. A sample consisting of 66 students and 3 Physics teachers was used to obtain the data. Data were collected through observation, interviews, and the distribution of questionnaire surveys. The results of the needs analysis of students and Physics teachers regarding Android-based ethnophysics learning media that incorporates traditional dances from North Maluku into Physics subjects indicate that such media is indeed needed by both students and Physics teachers in one of the schools in Ternate, Indonesia.